The Role of E-Commerce For Entrepreneurs - Sadiqin, Amin; Rahayu, Cindy Septiana (CV. Proaksara Global Transeduka, 2024)
E-commerce is a business model that facilitates the purchase or sale of products or services through online platforms. The focus of this research is to examine the impact of e-commerce on the growth and enhancement of entrepreneurial ventures. The objective of this study is to understand the significance of e-commerce in business development and improvement. The findings of the research indicate that e-commerce plays a crucial role, leading entrepreneurs to continuously utilize it for the advancement and expansion of their businesses. The ease of operating e-commerce platforms and their valuable contribution to business operations make them an indispensable tool for entrepreneurs. Moreover, entrepreneurs only require an internet connection to stay connected to the website or online media platform where their business operates.